Analisis Perbedaan Efektivitas Hand Massage Dan Pemberian Aromaterapi Lavender Terhadap Penurunan Nyeri Pasien Kanker Payudara Di Murni Teguh Memorial Hospital - Damanik, Sofia Ardelia; Sagala, Lam Murni (Indonesian Trust Nursing Journal, 2024)
Breast cancer is a health problem that often occurs and often causes death. The objective of this study is to determine the differences in the effectiveness of hand massage and lavender aromatherapy on reducing pain in breast cancer patients at Murni Teguh Memorial Hospital. The research method is quasy experimental study with two groups pretest postest study design. In this design, the two groups assigned different treatments for this research. The results of this study indicate that there are differences in the effectiveness of hand massage and lavender aromatherapy on reducing patient’s pain where the average value (mean) of the decrease in the two groups was 2.95 in the aromatherapy group and 2.62 in the hand massage group. It is concluded that Lavender aromatherapy is more effectivewhen compared to hand massage.